2021
DOI: 10.12998/wjcc.v9.i9.2068
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus of Chinese Association for the Study of Pain on the non-opioid analgesics for chronic musculoskeletal pain

Abstract: Chronic musculoskeletal pain (CMP) is a common occurrence in clinical practice and there are a variety of options for the treatment of it. However, the pharmacological therapy is still considered to be a primary treatment. The recent years have witnessed the emergence of opioid crisis, yet there are no relevant guidelines on how to treat CMP with non-opioid analgesics properly. The Chinese Medical Association for the Study of Pain convened a panel meeting to develop clinical practice consensus for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…10,11 Recently, the Chinese Medical Association Pain Society, which regulated the development of treatment guidelines for clinical pain, has been focusing on promoting the treatment of musculoskeletal pain using non-opioid analgesics. 9 Recently, many primary studies and reviews reported on musculoskeletal pain management in Western societies. 7,[10][11][12][13] Considering the anatomical and physiological differences between Asian and Western populations, there were fewer reports on musculoskeletal pain in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10,11 Recently, the Chinese Medical Association Pain Society, which regulated the development of treatment guidelines for clinical pain, has been focusing on promoting the treatment of musculoskeletal pain using non-opioid analgesics. 9 Recently, many primary studies and reviews reported on musculoskeletal pain management in Western societies. 7,[10][11][12][13] Considering the anatomical and physiological differences between Asian and Western populations, there were fewer reports on musculoskeletal pain in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids were no longer recommended in treating musculoskeletal pain due to the increased risk of adverse reactions and treatment interruptions 10,11 . Recently, the Chinese Medical Association Pain Society, which regulated the development of treatment guidelines for clinical pain, has been focusing on promoting the treatment of musculoskeletal pain using non‐opioid analgesics 9 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations